Factors Influencing the Incidence of Stunting Among Children Aged 24-59 Months in 2024 - Magno, Jerminal; Silva, Valente da; Nahak, Martinus (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Stunting or poor linear growth is considered a common health problem among children globally. Based on secondary data from Centro Saude Comunitaria Comoro from January-May 2024, it shows that there are 376 cases of stunting prevalence in children aged 24-59 months. Objective: To find out the factors that affect the incidence of stunting in toddlers aged 24-59 months at Suco Manleuana, Posto Administrativo Dom Aleixo, Municipio Dili, in 2024. Method:  The research design used in this study is aquantitative analytical research with a cross-sectional approach, which is a research that emphasizes the time to measure/observe independent and dependent variable data only once at a time. Result and Discussion: the study showed that there was a significant influence between education factors on stunting with a value of 0.002<0.05, there was a significant influence between family income factors on stunting with a value of 0.000<0.05, there was a significant influence between feeding pattern factors on stunting with a value of 0.000<0.05 and there was a significant influence between exclusive breastfeeding factors on stunting with a value of 0.000<0.05. Conclusion: that educational factors, family income factors, feeding pattern factors and exclusive breastfeeding factors have an influence on the incidence of stunting in toddlers aged 24-59 months in Suco Manleuana, Posto Administrativo Dom Aleixo, Municipio Dili, 2024. Therefore, it is recommended to the authorities to follow up to reduce or solve health problems, especially stunting in certain areas.